Application of the Diagnostic Evaluation for Alopecia in Traditional Veterinary Species to Laboratory Rhesus Macaques (Macaca mulatta) - Luchins, Kerith R (American Association for Laboratory Animal Science, 2011)
Alopecia in nonhuman primates in the biomedical research setting is often attributed to compromised psychologic wellbeing. Behavioral causes, mainly hair plucking, have become the unconfirmed and exclusive default diagnosis, and the possibility that alopecia may be secondary to a primary medical or dermatologic disease is often overlooked. Although nonbehavioral causes of alopecia in nonhuman primates are described in the literature, few prospective hypothesis-based studies have investigated medical and behavioral etiologies concurrently. We therefore undertook such a study with the aim of designing a clinical diagnostic guide for approaching cases of nonhuman primate alopecia. Because most cases of alopecia in nonhuman primates in the literature and at our facility are not associated with a definitive diagnosis, the hypothesis we tested was that the well-established diagnostic evaluation for alopecia used for traditional veterinary species is not applicable to nonhuman primates. Discounting differences in histopathology and behavioral assessment, the current study revealed few clinically relevant significant differences between nonhuman primates with and without alopecia. As a result, our hypothesis was confirmed, and we conclude that the standard dermatologic diagnostic plan typically described for alopecia diagnosis in traditional veterinary species and used as the basis for assessment of alopecia in nonhuman primates should be reassessed.